Hubungan Tingkat Pengetahuan Pengasuh dengan Pola Asuh Makan dan Status Gizi Balita di Puskesmas Sangkrah Surakarta - Wicaksono, Agil Wahyu; Prasetyawati, Arsita Eka; Damayanti, Kusmadewi Eka (Nexus Kedokteran Komunitas, 2013)
Background:Recently the role of mothers in child parenting replace by caregivers because many mothers also act as workforces. The role of parenting especially during meal is very important in determining the nutritional status of children. This studyaim is to determine whetherlevel ofknowledgehas strong relationshipwithfeeding patternandnutritional status of children. Methods:This studyis anobservationalstudywith crosssectionalanalytic. The researchwas conducted inApril-June2013 in theworking area ofSangkrahHealth Center, Surakarta. Sample of121caregiversandtheir childrenwereselectedby multistage areasampling .Examined variables includingcaregiverâslevelof knowledgeas independent variable, and feeding patternandnutritional status of childrenas dependent variable. ThisresearchusesCaregiverâsFeedingStyleQuestionnairetodeterminefeeding patternandQuestionnaire of Knowledge Leveltomeasure thelevel ofcaregiverâsknowledge. Bothquestionnaireshave beentestedfor validity and reliability. Nutritional status ismeasuredbystandard anthropometry method. Data wereanalyzedby SPSS 17 for Windows usingKendalls Taumodels. Results:This studyshows there is no significant correlation between the degree ofcaregiverâs knowledge andfeeding pattern(correlation coefficientÂ  = 0.132; degree of significance = 0.110) besides there is also no significant correlation between the degree ofcaregiverâs knowledgeand childrenâsnutritional status(correlation coefficient = 0.030; degree of significance = 0.716). Conclusions:There is nostatistically significantrelationshipbetween thedegree ofcaregiverâsknowledgewithfeeding patternandthe nutritional status ofchildren. Keywords:Degree of caregiverâs knowledge, feeding pattern, nutritional status of children. Â